Socialization of the Beginning Teacher: A Theoretical Model from the Empirical Literature - Russel Quaglia (Journal of Research in Rural Education, 1988)
The first year of teaching has been described as a time of survival for the beginning teacher, one of the most difficult and critical periods in a teacher's career (Veenman, 1984). It is during this transition that the teacher begins to develop the skills and habits that form the foundation for future teaching success. It is also during this time that many beginning teachers get discouraged and abandon their teaching careers. Thus, the appropriate solution to the problem of retention of academically able teachers is the improvement of school conditions and the provisions of support for beginning teachers. Current organizational practices do not adequately ease the transition of beginning teachers into the educational profession. To understand the processes by which teachers cope with entry and socialization experiences, a perspective to examine key features of the beginning teacher's experience is identified in this study.